In Memory of Bernard Bauchet 1955-2025 - Henket, Hubert-Jan (Docomomo Journal, 2025)
In February, Bernard Bauchet, a pioneer restoration architect of French Modern Movement buildings, passed away. In him we lose a knowledgeable and amiable person. He was involved, in one or another way, in all important projects of the rich French Moden Movement legacy. He restored la Maison de Verre by Chareau and Bijvoet, and published the book “la Maison de Verre” (GA publishers). He was responsible for the restoration and renovation of la Maison du Brésil by le Corbusier, Lucio Costa’s work in the Cité Universitaire in Paris, the Unité d’Habitation (first tranche) by le Corbusier in Brieu en Foret, and several other buildings by le Corbusier, Robert Mallet Stevens, Jean Lurçat and Auguste Peret. For the haute couture house of Azzedine Alaïa he did the transformation and renovation of the old warehouses by Victor Baltard in Paris 4th. I had the pleasure to cooperate with Bernard on the restoration of la Maison de Theo van Doesburg in Meudon, and together we participated in the scientific committee of the restoration and renovation of le Collège Néerlandais by Willem Dudok in the Cité Universitaire in Paris. Bernard was a member of other commitees as well, such as the Commission Nationale des Monuments Historiques (collège Mouvement Moderne), the expert committee of the Fondation le Corbusier, the scientific committee of la Maison E1027 by Eileen Gray in Roquebrune, and la Maison du Peuple by Beaudouin-Lods and Jean Prouvé in Clichy. He published various articles and participated in the international Docomomo conferences in New York and Ankara. Bernard’s curiosity and enthusiasm to learn and understand the motivation of the original architect he was dealing with, together with his knowledge of materials and implementation techniques made him extraordinary in the orbit of the Modern Movement. As the representative of la Maison Azzedine Alaïa wrote: “Bernard Bauchet était un architect exceptional, un homme d’un talent et d’une humaité rare.”